Antioxidant Activity of Six Marine Sponges Collected from the Persian Gulf: Antioxidant activity of marine sponges - Hassan Seradj; Mahmoodreza Moein; Masoumeh Eskandari; Faramarz Maaref (Iranian Journal of Pharmaceutical Sciences, 2012)
Compounds especially from natural sources are capable of protecting against reactive oxygen species (ROS) mediated damage. Therefore, there is a growing interest in novel substances exhibiting antioxidant properties. Several marine environments can provide a rich source of novel biologically active compounds. The aim of this paper is to evaluate in vitro antioxidant properties of six sponge species collected from Kish Island in the Persian Gulf. We evaluated the effects of different concentrations of the dichloromethane and methanolic extracts of six sponges on scavenging DPPH and OH free radicals. The activities of these extracts were compared with those of commercial antioxidants such as gallic acid. The maximum level of DPPH radical scavenging (0.234± 0.033 mg/ml) was observed for the methanolic extract of Pseudosaberites clavatus in the reaction mixture. Also, most of sponge extracts exhibited medium to high hydroxyl radical scavenging activity. The results of this study suggest that marine sponges of the Persian Gulf are promising sources of antioxidants.